2019
DOI: 10.1111/bph.14830
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting nucleolin reduces inflammation induced by mitochondrial DNA in cardiomyocytes exposed to hypoxia and reoxygenation

Abstract: Background and purpose Cellular debris causes sterile inflammation after myocardial infarction. Mitochondria constitute about 30 percent of the human heart. Mitochondrial DNA (mtDNA) is a damage‐associated‐molecular‐pattern that induce injurious sterile inflammation. Little is known about mtDNA's inflammatory signalling pathways in cardiomyocytes and how mtDNA is internalized to associate with its putative receptor, toll‐like receptor 9 (TLR9). Experimental Approach We hypothesized that mtDNA can be internaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…In particular, platelets activated by NETs release polyphosphates, which are prothrombotic and cause cardiac injury. Mitochondrial DNA also represents a trigger for inflammation after its internalization by cardiomyocytes, upregulating proinflammatory signaling pathways [57].…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…In particular, platelets activated by NETs release polyphosphates, which are prothrombotic and cause cardiac injury. Mitochondrial DNA also represents a trigger for inflammation after its internalization by cardiomyocytes, upregulating proinflammatory signaling pathways [57].…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Like bacterial DNA, mitochondrial DNA (mtDNA) is circular and enriched in CpG motifs (53). Our group demonstrated that circulating mtDNA increases in patients after myocardial infarction (54), extracellular mtDNA induced death of mouse cardiomyocytes via TLR9-dependent activation of NF-kB (55) and that inhibition of extracellular mtDNA uptake reduces inflammation in cardiomyocytes challenged with hypoxia/reperfusion (56). Accumulation of mtDNA in the heart promotes heart failure in a mouse model of pressure overload (53).…”
Section: Innate Immunity: Tlr9 Signaling and Endogenous Mitochondrialmentioning
confidence: 99%
“…Interestingly, AGER is involved in p66ShcA-dependent oxidative stress under some pathological conditions (140). Another mechanism of mtDNA delivery into cardiomyocytes is by the nucleolin (56). Our group has recently shown that nucleolin is expressed on cardiomyocyte membrane (56) and has an affinity to extracellular mtDNA and nDNA (141).…”
Section: Role Of Dna Transporters In Ischemic Heart Diseasementioning
confidence: 99%
“…The ability of CpG‐rich mitochondrial DNA to trigger TLR9 activation has led to the appropriate use of CpG‐ODN for the study of multiple disease states where mitochondrial stress and injury are believed to play a pathogenic role 51–56 . These include atherosclerosis, 10–14 ischaemia‐reperfusion, 11,15–19,94 infection/sepsis, 20–37 and various autoimmune diseases 38–50 . Due to the direct link between mitochondrial stress and intracellular calcium dyshomeostasis, 84–86 the effect of intracellular calcium on CpG‐ODN‐mediated innate immune signalling is relevant to the study of these disease states associated with sterile inflammation.…”
Section: Discussionmentioning
confidence: 99%